Chapter Note al testo e alla traduzione - Graziani, Michela (Studi di Traduzione Letteraria Lusofona, 2023)
The aim of this article is to offer some useful notes about the two collections of sonnets here translated, together with some commentaries concerning the translation work undertaken.